1997
DOI: 10.2307/1592441
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Comparisons of the Variable VP2 Region of Eight Infectious Bursal Disease Virus Isolates

Abstract: The VP2 gene is part of the genomic segment A of infectious bursal disease virus (IBDV). It has been identified as the major host-protective antigen of IBDV and is known to contain conformationally dependent protective epitopes. A 643-base pair segment covering the hypervariable region of this gene from three recent serologic variant IBDV isolates from the southeastern United States, two variants from the Delmarva Peninsula, and three serologic standard viruses were amplified and sequenced using the reverse tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…Among these proteins, the structural protein VP2 has been identified as the major host-protective immunogen of IBDV [2,4]. Sequence analysis of VP2 genes of various isolates showed that changes in the center of VP2 account for antigenic or pathogenic variations of IBDV [3,5,7,9,10,20,27,30,31].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among these proteins, the structural protein VP2 has been identified as the major host-protective immunogen of IBDV [2,4]. Sequence analysis of VP2 genes of various isolates showed that changes in the center of VP2 account for antigenic or pathogenic variations of IBDV [3,5,7,9,10,20,27,30,31].…”
mentioning
confidence: 99%
“…1, the Vietnamese virulent strain 17a and the classical strain 52/70 had only one amino acid substitution in the hydrophobic matrix (residue 254, serine in 17a and glycine in 52/70). Dormitorio et al [9] reported the only change that could distinguish the variants from the standard isolates is in residue 254, which changed from glycine in the standard isolates to serine in the variants. Further studies on antigenicity of this Vietnamese strain and the others are necessary to elucidate the epidemiology of IBDV in Vietnam.…”
mentioning
confidence: 99%
“…The trend of mutation is followed naturally in the existing genetic pool of Indo-Pak region [8]. Some of US variant and French vvIBDVs matched the similar ongoing change [9,41]. Shabir and co-workers reported that Histidine, amino acid (H) is located at position 221 [33] is characteristic for Pakistani strains.…”
Section: Discussionmentioning
confidence: 99%
“…Selected sequences were aligned by Neighbour-Joining (NJ) Method. This information provides many important aspects [2,9,10]. Topologically, the phylogenetic tree revealed that IBDVs separated into three main groups, namely vvIBD viruses, classic/variant viruses and attenuated/vaccine strains.…”
Section: Phylogenetic Analysis Of Vp2-hvrmentioning
confidence: 99%
See 1 more Smart Citation